GLOBAL INNOVATION MANAGEMENT IN THE CONTEXT OF ENCOURAGING THE DEVELOPMENT OF REGENERATIVE AGRIFOOD SYSTEMS (INNOVATIVE ECONOMY, 2024)
Shkolnyi O.O. GLOBAL INNOVATION MANAGEMENT IN THE CONTEXT OF ENCOURAGING THE DEVELOPMENT OF REGENERATIVE AGRIFOOD SYSTEMSPurpose. The purpose of the article is to generalize the practice of supporting sustainable global competitive advantage due to the mechanisms of global innovation management aimed at encouraging the development of regenerative agrifood systems.Methodology of research. As a scientific method of cognition, system analysis has been involved as the theoretical and methodological basis of the research. General scientific and special methods were used during the research, particularly: induction and deduction – at the stage of collecting primary data and analyses; abstract thinking and logical analysis – in the process of formulating conclusions in respect to advantages of agrifood systems with the focus on the development of regenerative agriculture; monographic – to summarize the practice of global companies in achieving competitive advantage by stimulating the development of regenerative agrifood systems, graphical – to illustrate the process of achieving sustainable global competitive advantage due to mechanisms of global innovation management aimed at encouraging the development of regenerative agrifood systems.Findings. The effects of the negative impact of industrial agriculture were identified, and the needs in stimulation of regenerative agrifood systems’ development were revealed. The necessity of observing the principles of HR’s social development and the reflections of social values in entrepreneurial activities of global companies have been determined. The main attention is focused on the growing threat of environmental problems, global warming and changes in the world water cycle, which reflects the urgency of applying innovative management mechanisms to solve the urgent problems of the agrarian sector of the economy. The need for the formation of business models focused on the circular economy and the sustainable development of the agrifood sector has been revealed. Forecast data related to sale volumes of products produced on the basis of regenerative agriculture technologies around the world were analyzed. The experience of global companies in the formation of regenerative agriculture development projects has been summarized. The possibilities of the formation of sustainable competitive advantage due to the mechanisms of global innovation management aimed at stimulating the development of regenerative agrifood systems were highlighted.Originality. The conceptual approaches to understanding the role of global innovation management in stimulating the development of regenerative agrifood systems were deepened. The scientific and methodological approaches to the analysis of the dialectical relationship between the concepts of corporate social responsibility, global innovation management and the basic principles of the development of regenerative agrifood systems have been improved.Practical value. The theoretical and methodological approaches and recommendations related to the development of regenerative agrifood systems can become the basis for the implementation of methods of strategic positioning of the global companies on the world markets and for the further scientific investigations on these issues.Key words: global environmental problems, global innovation management, regenerative agrifood systems; sustainable competitive advantage, global positioning.
Keywords: global environmental problems; global innovation management; regenerative agrifood systems; sustainable competitive advantage; global positioning.